Method and device for preparing high-purity high-stability few-layer 1T-phase MoS2 nanosheet sodium-ion battery negative electrode material by one-step alcohol-thermal method

The preparation of high-purity, high-stable, and low-layer 1T-phase MoS2 nanosheets was solved by a one-step alcohol thermal method, and the material instability and kinetics problems in the negative electrode materials of sodium ion battery were achieved, high energy density and excellent rate performance were achieved, and the application potential of the material was significantly improved.

CN119528221APending Publication Date: 2025-02-28HUAINAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411699188.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing sodium ion battery anode materials face serious problems of crushing and slow transmission dynamics, resulting in low reversible capacity and fast capacity attenuation. The 1T phase MoS2 is not stable enough under natural conditions and is difficult to synthesize effectively.

Method used

A high-purity, high-stable, low-layer 1T-phase MoS2 nanosheet was prepared by a one-step alcohol heat method. The precursor solution was prepared by ultrasonic stirring in anhydrous ethanol, and insulated at 210°C for 18 hours to obtain a high-purity 1T-phase MoS2 nanosheet.

Benefits of technology

The obtained small-layer 1 T-phase MoS2 nanosheets exhibit excellent sodium storage and rate performance in the negative electrode materials of sodium ion battery, and can achieve a specific capacity of 311.6mAh g-1 at a high current density of 10A g-1, significantly improving the application potential of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528221A_ABST
    Figure CN119528221A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion battery negative electrode materials, and discloses a method and a device for preparing a high-purity and high-stability few-layer 1T-phase MoS2 nanosheet sodium ion battery negative electrode material by a one-step alcohol-thermal method, namely a precursor solution of 1T-phase MoS2 is prepared by adopting absolute ethyl alcohol as a solvent, and the high-purity and high-stability few-layer 1T-phase MoS2 nanosheet is obtained by the one-step alcohol-thermal method. When the few-layer 1T-phase MoS2 nanosheet prepared by the method is used as a sodium ion battery negative electrode material, the specific capacity can reach 311.6 mAh g <-1 > under the high current density of 10A g <-1 >, and the few-layer 1T-phase MoS2 nanosheet shows excellent rate capability and shows extremely high application potential in the field of sodium ion battery negative electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing negative electrode materials for sodium ion batteries, and in particular to a method and device for preparing high-purity and high-stability few-layer 1T phase MoS2 nanosheet negative electrode materials for sodium ion batteries by a one-step alcohol thermal method, belonging to the field of preparation of negative electrode materials for sodium ion batteries. Background Art

[0002] Recently, sodium-ion batteries have attracted extensive attention in the field of energy storage due to their advantages such as high energy density, high safety, and abundant sodium resources. Usually, the electrode materials of sodium-ion batteries face serious problems of crushing and slow transport kinetics, resulting in low reversible capacity and rapid capacity decay. Therefore, researchers are eager to seek more advanced electrode materials for sodium-ion batteries. For the negative electrode materials of sodium-ion batteries, commercial graphite can only show a capacity as low as 35 mAh g -1 The sodium storage capacity of hard carbon is limited (200-300 mAh g -1 ), still cannot meet the development needs of high energy density sodium ion batteries. Therefore, seeking new high-performance negative electrode materials has become one of the hot topics in cutting-edge research.

[0003] MoS2 has a unique layered structure with an interlayer spacing of 0.62 nm, which can achieve rapid diffusion of sodium ions and a high theoretical capacity (670 mAh g -1 ), becoming an ideal candidate system for negative electrode materials for sodium ion batteries. According to the different coordination forms of Mo and S, MoS2 is mainly divided into two crystal phases: 2H phase (triangular prismatic structure) and 1T phase (octahedral coordination structure). Among them, 2H phase MoS2 is a thermodynamically stable phase and is easy to synthesize due to its low formation energy. However, it has a large band gap (1.9 eV) and exhibits semiconductor properties. As a negative electrode material for sodium ion batteries, its sluggish diffusion kinetics, continuous sulfur dissolution, and poor reaction reversibility lead to significant material capacity attenuation and poor rate performance during the cycle. In contrast, 1T phase MoS2 has metallic high conductivity characteristics and a larger interlayer spacing, which is more conducive to Na +Diffusion, making it a candidate system for negative electrode materials of sodium ion batteries. However, the thermodynamic metastable phase characteristics of 1T phase MoS2 under natural conditions make it difficult to synthesize stably, which greatly limits its further application development. In order to obtain 1T phase MoS2, methods such as mechanical exfoliation, alkali metal intercalation exfoliation, electron injection and hydrothermal methods have been widely studied in previous work. However, the proportion of 1T phase obtained by these methods generally does not exceed 80%. More importantly, the obtained 1T phase MoS2 is not stable enough under natural conditions and will gradually transform into 2H phase. In addition, the process is also relatively complicated, with high pollution and low yield, which is not conducive to the practical application of materials. Therefore, it is of great research significance to explore a novel, simple and environmentally friendly preparation method to prepare high-purity and high-stable 1T phase MoS2 and obtain excellent sodium storage performance. Summary of the invention

[0004] Based on the above problems, the present invention provides a method and device for preparing high-purity and high-stability few-layer 1T phase MoS2 nanosheets as negative electrode materials for sodium ion batteries by a one-step alcohol thermal method. The obtained few-layer 1T phase MoS2 nanosheets show excellent sodium storage performance as negative electrode materials for sodium ion batteries. -1 The specific capacity can reach 311.6 mAh g at ultra-high current density. -1 , showing excellent rate performance and showing great application potential in the field of sodium ion battery negative electrode materials.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] A method and device for preparing high-purity and high-stability few-layer 1T phase MoS2 nanosheet sodium ion battery negative electrode material by a one-step alcohol thermal method, comprising the following steps:

[0007] S1. Preparing a precursor solution: adding ammonium molybdate tetrahydrate as a Mo source and thiourea as a S source into an anhydrous ethanol solvent, ultrasonicating and stirring to obtain a precursor solution for preparing 1T phase MoS2;

[0008] S2. Preparation of few-layer 1T phase MoS2 nanosheets: transfer the precursor solution to a reactor, heat it to 210°C, and keep it warm for 18 hours. Wash the obtained black precipitate with deionized water and ethanol for 3 times each, collect it by centrifugation, and then place it in a vacuum oven at 60°C to dry it for 12 hours. After drying, few-layer 1T phase MoS2 nanosheets are obtained.

[0009] On the basis of the above technical solution, the present invention has the following further limitations:

[0010] Furthermore, the molar ratio of ammonium molybdate tetrahydrate to thiourea in step S1 is 1:30.

[0011] Furthermore, the ultrasound in step S1 is ultrasound with an ultrasonic cleaner for 30 minutes; and the stirring is magnetic stirring for 1 hour.

[0012] Furthermore, the reaction process in step S2 is a one-step alcohol thermal process rather than a multi-step reaction process with ethanol solvent post-treatment.

[0013] Furthermore, the black precipitate of the reaction product in step S2 is a high-purity and highly stable few-layer 1T phase MoS2 nanosheet material, rather than other forms of 1T and 2H mixed phase MoS2 material.

[0014] Furthermore, the washing in step S2 is washing with deionized water and ethanol for 3 times each; the drying is performed at 60° C. and vacuum drying for 12 hours.

[0015] Furthermore, in step S1, the reaction temperature is 210° C. and the insulation time is 18 h.

[0016] Furthermore, the solvent in step S1 is only anhydrous ethanol without any deionized water or other solvents, wherein the volume of the ethanol solvent is 2-20 mL, preferably 18 mL.

[0017] A device for preparing high-purity and high-stability few-layer 1T phase MoS2 nanosheet sodium ion battery negative electrode material by a one-step alcohol thermal method, using the above-mentioned preparation method, comprising:

[0018] A main body, wherein a stepped chamber with openings at the top and bottom is provided inside the main body, and a pressurizing channel arranged vertically with the stepped chamber is also provided thereon, so that the stepped chamber is divided into an upper chamber and a lower chamber;

[0019] A pressurized connector, which is disposed on both sides of the main body, corresponding to the position of the pressurized channel, one end of which is connected to an external pressurized device, and the other end of which is connected to the pressurized channel;

[0020] A first pressure-resistant component, which is disposed in the upper chamber, has first protrusions on both sides thereof, and is connected to the main body through the first protrusions;

[0021] A second pressure-resistant component, which is disposed in the lower chamber, has second protrusions on both sides thereof, is connected to the main body through the second protrusions, and is symmetrically arranged with the first pressure-resistant component;

[0022] A first sealing member, which is sleeved on the first pressure-resistant component and the second pressure-resistant component respectively, is located between the first pressure-resistant component, the second pressure-resistant component and the main body, and is in contact with the first protrusion and the second protrusion respectively;

[0023] a second sealing member, wherein the second sealing member is sleeved on the first pressure-resistant member and the second pressure-resistant member, respectively, and is located between the first pressure-resistant member, the second pressure-resistant member and the main body, and is in contact with the first sealing member;

[0024] A first upper gland, which is disposed in the upper chamber and sleeved on the first pressure-resistant component, and whose bottom contacts the second sealing member;

[0025] A first lower gland, which is disposed in the lower chamber and sleeved on the second pressure-resistant component, with a top in contact with the second sealing member;

[0026] A second upper gland, wherein the center of the second upper gland is provided with an observation channel, the bottom of which is respectively connected to the first pressure-resistant component and the first upper gland, and the second upper gland is connected to the main body by a threaded connection;

[0027] The second lower pressure cover has an observation channel at its center, and the top of the second lower pressure cover is respectively connected to the second pressure-resistant component and the first lower pressure cover, and is threadedly connected to the main body.

[0028] Furthermore, the main body, the first pressure-resistant component and the second pressure-resistant component are made of transparent pressure-resistant material.

[0029] The beneficial effect of the present invention is that a high-purity and high-stability few-layer 1T phase MoS2 nanosheet is prepared by a one-step alcohol thermal method. The preparation method is simple in process, low in cost, and environmentally friendly, and is expected to achieve industrial production and meet commercial needs. When the few-layer 1T phase MoS2 nanosheet prepared by the present invention is used as a negative electrode material for sodium ion batteries, it exhibits excellent rate performance, which is much higher than the current commercial hard carbon negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 X-ray diffraction patterns of the T-phase MoS2 sample of Example 11 of the present invention and the H-phase MoS2 sample of Comparative Example 12;

[0031] Figure 2 This is a scanning electron microscope image of the surface morphology of the few-layer 1T phase MoS2 nanosheet sample of Example 1 of the present invention;

[0032] Figure 3 This is a comparison chart of the rate performance of the T-phase MoS2 sample of Example 11 of the present invention and the H-phase MoS2 sample of Comparative Example 12 as negative electrode materials for sodium ion batteries;

[0033] Figure 4 This is a schematic diagram of the structure of the preparation device in Example 7 of the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] The method for preparing a high-purity and high-stability few-layer 1T phase MoS2 nanosheet sodium ion battery negative electrode material by a one-step alcohol thermal method comprises the following steps:

[0037] S1. Prepare a precursor solution: add 0.3056 g of ammonium molybdate tetrahydrate as a Mo source and 0.599 g of thiourea as a S source into 18 mL of anhydrous ethanol solvent, ultrasonicate and stir to obtain a precursor solution for preparing 1T phase MoS2;

[0038] S2. Preparation of few-layer 1T phase MoS2 nanosheets: transfer the precursor solution to a reactor, heat it to 210°C, and keep it warm for 18 hours. Wash the obtained black precipitate with deionized water and ethanol for 3 times each, collect it by centrifugation, and then place it in a vacuum oven at 60°C to dry it for 12 hours. After drying, few-layer 1T phase MoS2 nanosheets are obtained.

[0039] Example 2

[0040] The method for preparing a high-purity and high-stability few-layer 1T phase MoS2 nanosheet sodium ion battery negative electrode material by a one-step alcohol thermal method comprises the following steps:

[0041] S1. Prepare a precursor solution: Take 0.3056 g of ammonium molybdate tetrahydrate as a Mo source and 0.599 g of thiourea as a S source, add them into 2 mL of anhydrous ethanol solvent, ultrasonicate and stir to obtain a precursor solution for preparing 1T phase MoS2;

[0042] S2. Preparation of few-layer 1T phase MoS2 nanosheets: transfer the precursor solution to a reactor, heat it to 210°C, and keep it warm for 18 hours. Wash the obtained black precipitate with deionized water and ethanol for 3 times each, collect it by centrifugation, and then place it in a vacuum oven at 60°C to dry it for 12 hours. After drying, few-layer 1T phase MoS2 nanosheets are obtained.

[0043] Example 3

[0044] The method for preparing a high-purity and high-stability few-layer 1T phase MoS2 nanosheet sodium ion battery negative electrode material by a one-step alcohol thermal method comprises the following steps:

[0045] S1. Prepare a precursor solution: Take 0.3056 g of ammonium molybdate tetrahydrate as a Mo source and 0.599 g of thiourea as a S source, add them into 5 mL of anhydrous ethanol solvent, ultrasonicate and stir to obtain a precursor solution for preparing 1T phase MoS2;

[0046] S2. Preparation of few-layer 1T phase MoS2 nanosheets: transfer the precursor solution to a reactor, heat it to 210°C, and keep it warm for 18 hours. Wash the obtained black precipitate with deionized water and ethanol for 3 times each, collect it by centrifugation, and then place it in a vacuum oven at 60°C to dry it for 12 hours. After drying, few-layer 1T phase MoS2 nanosheets are obtained.

[0047] Example 4

[0048] The method for preparing a high-purity and high-stability few-layer 1T phase MoS2 nanosheet sodium ion battery negative electrode material by a one-step alcohol thermal method comprises the following steps:

[0049] S1. Prepare a precursor solution: Take 0.3056 g of ammonium molybdate tetrahydrate as a Mo source and 0.599 g of thiourea as a S source, add them into 10 mL of anhydrous ethanol solvent, ultrasonicate and stir to obtain a precursor solution for preparing 1T phase MoS2;

[0050] S2. Preparation of few-layer 1T phase MoS2 nanosheets: transfer the precursor solution to a reactor, heat it to 210°C, and keep it warm for 18 hours. Wash the obtained black precipitate with deionized water and ethanol for 3 times each, collect it by centrifugation, and then place it in a vacuum oven at 60°C to dry it for 12 hours. After drying, few-layer 1T phase MoS2 nanosheets are obtained.

[0051] Example 5

[0052] The method for preparing a high-purity and high-stability few-layer 1T phase MoS2 nanosheet sodium ion battery negative electrode material by a one-step alcohol thermal method comprises the following steps:

[0053] S1. Prepare a precursor solution: Take 0.3056 g of ammonium molybdate tetrahydrate as a Mo source and 0.599 g of thiourea as a S source, add them into 15 mL of anhydrous ethanol solvent, ultrasonicate and stir to obtain a precursor solution for preparing 1T phase MoS2;

[0054] S2. Preparation of few-layer 1T phase MoS2 nanosheets: transfer the precursor solution to a reactor, heat it to 210°C, and keep it warm for 18 hours. Wash the obtained black precipitate with deionized water and ethanol for 3 times each, collect it by centrifugation, and then place it in a vacuum oven at 60°C to dry it for 12 hours. After drying, few-layer 1T phase MoS2 nanosheets are obtained.

[0055] Example 6

[0056] The method for preparing a high-purity and high-stability few-layer 1T phase MoS2 nanosheet sodium ion battery negative electrode material by a one-step alcohol thermal method comprises the following steps:

[0057] S1. Prepare a precursor solution: add 0.3056 g of ammonium molybdate tetrahydrate as a Mo source and 0.599 g of thiourea as a S source into 20 mL of anhydrous ethanol solvent, ultrasonicate and stir to obtain a precursor solution for preparing 1T phase MoS2;

[0058] S2. Preparation of few-layer 1T phase MoS2 nanosheets: transfer the precursor solution to a reactor, heat it to 210°C, and keep it warm for 18 hours. Wash the obtained black precipitate with deionized water and ethanol for 3 times each, collect it by centrifugation, and then place it in a vacuum oven at 60°C to dry it for 12 hours. After drying, few-layer 1T phase MoS2 nanosheets are obtained.

[0059] Example 7

[0060] The method and steps in the above embodiment are used, wherein a device for preparing a high-purity and high-stability few-layer 1T phase MoS2 nanosheet sodium ion battery negative electrode material by a one-step alcohol thermal method comprises:

[0061] The main body 1 is a columnar structure made of a transparent material. A stepped chamber with openings at the top and bottom is provided inside the main body 1, and a pressurizing channel 2 arranged vertically to the stepped chamber is also provided thereon, so that the stepped chamber is divided into an upper chamber and a lower chamber. In other words, both the upper chamber and the lower chamber are stepped chamber structures;

[0062] The pressurized connector is such as a connector, which is disposed on both sides of the main body 1, corresponding to the position of the pressurized channel 2, one end of which is connected to an external pressurized device, and the other end is connected to the pressurized channel 2;

[0063] The first pressure-resistant component 3 is a transparent block structure, and can be made of sapphire or the like, which is not limited here. The first pressure-resistant component 3 is arranged in the upper chamber, and has first protrusions on both sides thereof, and is connected to the main body 1 through the first protrusions;

[0064] The second pressure-resistant component 4 is a transparent block structure, and can be made of sapphire or the like, which is not limited here. The second pressure-resistant component 4 is arranged in the lower chamber, and has second protrusions on both sides thereof, and is connected to the main body 1 through the second protrusions. The second pressure-resistant component 4 is symmetrically arranged with the first pressure-resistant component 3;

[0065] It should be noted that the first pressure-resistant component 3 and the second pressure-resistant component 4 are fixed in the upper chamber and the lower chamber respectively by step-clamping, wherein a pressure chamber is formed by a gap between the bottom of the first pressure-resistant component 3 and the top of the second pressure-resistant component 4, and the area of ​​the pressure chamber should be less than or equal to the area of ​​the pressure channel 2, preferably equal to;

[0066] The first sealing member 5 is such as an O-ring, and the first sealing member 5 is respectively sleeved on the first pressure-resistant component 3 and the second pressure-resistant component 4, and is located between the first pressure-resistant component 3, the second pressure-resistant component 4 and the main body 1, and is in contact with the first protrusion and the second protrusion respectively;

[0067] The second sealing member 6 is a sealing rubber pad, which is respectively sleeved on the first pressure-resistant component 3 and the second pressure-resistant component 4, and is located between the first pressure-resistant component 3, the second pressure-resistant component 4 and the main body 1, and is in contact with the first sealing member 5;

[0068] The first upper pressure cover 7 is an annular block structure, and the first upper pressure cover 7 is arranged in the upper chamber, and is sleeved on the first pressure-resistant component 3, and its bottom is in contact with the second sealing member 6;

[0069] The first lower pressure cover 8 is an annular block structure, and the first lower pressure cover 8 is arranged in the lower chamber, and is sleeved on the second pressure-resistant component 4, and the top of the first lower pressure cover 8 is in contact with the second sealing member 6;

[0070] A second upper gland 9, wherein an observation channel is provided at the center of the second upper gland 9, and the bottom of the second upper gland 9 is respectively connected to the first pressure-resistant component 3 and the first upper gland 7, and the second upper gland 9 is connected to the main body 1 by threads;

[0071] The second lower pressure cover 10 has an observation channel at its center, and the top of the second lower pressure cover 10 is respectively connected to the second pressure-resistant component 4 and the first lower pressure cover 8 , and is threadedly connected to the main body 1 .

[0072] When in use, the second upper pressure cover 9 and the second lower pressure cover 10 are rotated to move longitudinally inside the main body 1. At the same time, the second upper pressure cover 9 and the second lower pressure cover 10 respectively press the first upper pressure cover 7, the first lower pressure cover 8 and the first pressure-resistant component 3, the second pressure-resistant component 4, so as to improve the sealing effect of the pressurized chamber. The precursor liquid is placed in the pressurized chamber, and the pressurized chamber is pressurized or heated after being connected to the pressurized connector through an external pressurization or heating device, so that the precursor liquid in the pressurized chamber is processed and reacted. By using a mechanical high-pressure autoclave as a reactor, not only the structure is simpler, but also the operation is convenient and easy to observe, so that the user can record according to real-time changes. During the observation process, the changes of the precursor liquid in the pressurized chamber can be observed from the second upper pressure cover 9, the second lower pressure cover 10 or the main body 1 through a microscope, so as to record. Since the pressurized chamber is a linear structure, it is easy to achieve instantaneous high pressure and due to its sealing effect, the internal pressure of the pressurized chamber can be kept constant to a certain extent, achieving not only convenient operation but also improved reaction efficiency. Technical effect.

[0073] Comparative Example 1

[0074] The method for preparing 2H phase MoS2 by hydrothermal method comprises the following steps:

[0075] S1. Prepare a precursor solution: take 0.3056 g of ammonium molybdate tetrahydrate as a Mo source and 0.599 g of thiourea as a S source, add them into 18 mL of deionized water solvent, ultrasonicate and stir to obtain a precursor solution for preparing 2H phase MoS2;

[0076] S2. Preparation of 2H phase MoS2 nanosheets: transfer the precursor solution to a reactor, heat it to 210°C, and keep it warm for 18 hours. Wash the obtained black precipitate with deionized water and ethanol for 3 times each, collect it by centrifugation, and then place it in a vacuum oven at 60°C and dry it for 12 hours. After drying, 2H phase MoS2 nanosheets are obtained.

[0077] Performance comparison

[0078] The samples in Example 1 and Comparative Example 1 were subjected to X-ray diffraction and electrochemical performance tests, and the results were as follows: Figure 1 , Figure 3 shown.

[0079] The samples in Example 1 were observed by scanning electron microscope, and the results were as follows: Figure 2 shown.

[0080] Depend on Figure 1 It can be seen that the (002) peak of the 1T phase MoS2 sample shifts significantly to the left compared with the 2H phase MoS2, and the peak intensity becomes significantly weaker, indicating the formation of a few-layer 1T phase nanosheet structure.

[0081] Depend on Figure 2 It can be seen that the few-layer 1T phase MoS2 nanosheet sample exhibits a spherical nanosheet structure, in which the nanosheet size is about 100nm and the thickness is about several nm.

[0082] Depend on Figure 3 It can be seen that the rate performance of 1T phase MoS2 is significantly higher than that of 2H phase MoS2 control sample. -1 At a high current density of 311.6 mAh g -1 , indicating that the few-layer 1T phase MoS2 nanosheet samples significantly accelerated the diffusion dynamics of sodium ions due to their large interlayer spacing, high conductivity and ultra-small nanosheets, and effectively alleviated the large volume changes caused by the insertion or extraction of sodium ions.

[0083] As can be seen from the above, the few-layer 1T phase MoS2 nanosheet sodium ion battery negative electrode material obtained by the present invention has a high -1 The specific capacity can reach 311.6 mAh g at high current density. -1 , showing excellent rate performance and showing great application potential in the field of sodium ion battery negative electrode materials.

Claims

1. A method for preparing high-purity and high-stability few-layer 1T phase MoS2 nanosheets as a negative electrode material for sodium ion batteries by a one-step alcohol thermal method, characterized in that: The following steps are involved: S1. Preparing a precursor solution: adding ammonium molybdate tetrahydrate as a Mo source and thiourea as a S source into an anhydrous ethanol solvent, ultrasonicating and stirring to obtain a precursor solution for preparing 1T phase MoS2; S2. Preparation of few-layer 1T phase MoS2 nanosheets: transfer the precursor solution to a reactor, heat it to 210°C, and keep it warm for 18 hours. Wash the obtained black precipitate and collect it by centrifugation. After drying, obtain the few-layer 1T phase MoS2 nanosheets.

2. The method for preparing a high-purity and high-stability few-layer 1T phase MoS2 nanosheet sodium ion battery negative electrode material by a one-step alcohol thermal method according to claim 1, characterized in that: The molar ratio of ammonium molybdate tetrahydrate to thiourea in step S1 is 1:

30.

3. The method for preparing high-purity and high-stability few-layer 1T phase MoS2 nanosheet sodium ion battery negative electrode material by a one-step alcohol thermal method according to claim 1, characterized in that: The ultrasound in step S1 is performed by ultrasound machine for 30 minutes; and the stirring is performed by magnetic stirring for 1 hour.

4. The method for preparing a high-purity and high-stability few-layer 1T phase MoS2 nanosheet sodium ion battery negative electrode material by a one-step alcohol thermal method according to claim 1, characterized in that: The reaction process described in step S2 is a process in which the precursor is dissolved in an ethanol solvent under high temperature and high pressure conditions in a reactor to react and generate 1T phase MoS2 nanosheets. Therefore, it is defined as a one-step alcohol thermal method, rather than a multi-step process of first synthesizing the MoS2 material and then post-treating it with an ethanol solvent.

5. The method for preparing high-purity and high-stability few-layer 1T phase MoS2 nanosheet sodium ion battery negative electrode material by a one-step alcohol thermal method according to claim 1, characterized in that: The black precipitate of the reaction product described in step S2 is a high-purity and high-stability few-layer 1T phase MoS2 nanosheet material, rather than other forms of 1T and 2H mixed phase MoS2 material.

6. The method for preparing high-purity and high-stability few-layer 1T phase MoS2 nanosheet sodium ion battery negative electrode material by a one-step alcohol thermal method according to claim 1, characterized in that: The washing in step S2 is washing with deionized water and ethanol for 3 times each; the drying is vacuum drying at 60° C. for 12 hours.

7. The method for preparing high-purity and high-stability few-layer 1T phase MoS2 nanosheets sodium ion battery negative electrode material by a one-step alcohol thermal method according to claim 1, characterized in that: The reaction temperature in step S1 is 210° C. and the insulation time is 18 h.

8. The method for preparing high-purity and high-stability few-layer 1T phase MoS2 nanosheet sodium ion battery negative electrode material by a one-step alcohol thermal method according to claim 1, characterized in that: The solvent in step S1 is only anhydrous ethanol, without any deionized water or other solvents, wherein the volume of the ethanol solvent is 2-20 mL, preferably 18 mL.

9. A device for preparing high-purity and high-stability few-layer 1T phase MoS2 nanosheets as a negative electrode material for sodium ion batteries by a one-step alcohol thermal method, using the preparation method described in claims 1-8, characterized in that: include: A main body, wherein a stepped chamber with openings at the top and bottom is provided inside the main body, and a pressurizing channel arranged vertically with the stepped chamber is also provided thereon, so that the stepped chamber is divided into an upper chamber and a lower chamber; A pressurized connector, which is disposed on both sides of the main body, corresponding to the position of the pressurized channel, one end of which is connected to an external pressurized device, and the other end of which is connected to the pressurized channel; A first pressure-resistant component, which is disposed in the upper chamber, has first protrusions on both sides thereof, and is connected to the main body through the first protrusions; A second pressure-resistant component, which is disposed in the lower chamber, has second protrusions on both sides thereof, is connected to the main body through the second protrusions, and is symmetrically arranged with the first pressure-resistant component; A first sealing member, which is sleeved on the first pressure-resistant component and the second pressure-resistant component respectively, is located between the first pressure-resistant component, the second pressure-resistant component and the main body, and is in contact with the first protrusion and the second protrusion respectively; A second sealing member, which is sleeved on the first pressure-resistant component and the second pressure-resistant component respectively, is located between the first pressure-resistant component, the second pressure-resistant component and the main body, and is in contact with the first sealing member; A first upper gland, which is disposed in the upper chamber and sleeved on the first pressure-resistant component, and whose bottom contacts the second sealing member; A first lower gland, which is disposed in the lower chamber and sleeved on the second pressure-resistant component, with a top in contact with the second sealing member; A second upper gland, wherein the center of the second upper gland is provided with an observation channel, the bottom of which is respectively connected to the first pressure-resistant component and the first upper gland, and the second upper gland is connected to the main body by a threaded connection; The second lower pressure cover has an observation channel at its center, and the top of the second lower pressure cover is respectively connected to the second pressure-resistant component and the first lower pressure cover, and is threadedly connected to the main body.

10. The device for preparing high-purity and high-stability few-layer 1T phase MoS2 nanosheets sodium ion battery negative electrode material by a one-step alcohol thermal method according to claim 9, characterized in that: The main body, the first pressure-resistant component and the second pressure-resistant component are made of transparent pressure-resistant material.